Biowaiver Monograph for Immediate‐Release Solid Oral Dosage Forms: Bisoprolol Fumarate. Issue 2 (30th December 2013) - Charoo, Naseem A.; Shamsher, Areeg A. A.; Lian, Lai Y.; Abrahamsson, Bertil; Cristofoletti, Rodrigo; Groot, D. W.; Kopp, Sabine; Langguth, Peter; Polli, James; Shah, Vinod P.; Dressman, Jennifer
<x xml:space="preserve">Abstract</x> Literature data relevant to the decision to allow a waiver of in vivo bioequivalence (BE) testing for the approval of immediate‐release (IR) solid oral dosage forms containing bisoprolol as the sole active pharmaceutical ingredient (API) are reviewed. Bisoprolol is classified as a Class I API according to the current Biopharmaceutics Classification System (BCS). In addition to the BCS class, its therapeutic index, pharmacokinetic properties, data related to the possibility of excipient interactions, and reported BE/bioavailability problems are taken into consideration. Qualitative compositions of IR tablet dosage forms of bisoprolol with a marketing authorization (MA) in ICH (International Conference on Harmonisation) countries are tabulated. It was inferred that these tablets had been demonstrated to be bioequivalent to the innovator product. No reports of failure to meet BE standards have been made in the open literature. On the basis of all these pieces of evidence, a biowaiver can currently be recommended for bisoprolol fumarate IR dosage forms if (1) the test product contains only excipients that are well known, and used in normal amounts, for example, those tabulated for products with MA in ICH countries and (2) both the test and comparator dosage form are very rapidly dissolving, or, rapidly dissolving with similarity of the dissolution profiles demonstrated at pH 1.2, 4.5, and 6.8. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:378–391, 2014